Comment on "Fullerene-based materials for solar cell applications: design of novel acceptors for efficient polymer solar cells – a DFT study" by A. Mohajeri and A. Omidvar, Phys. Chem. Chem. Phys., 2015, 17, 22367. Issue 5 (18th January 2016) - Sabirov, Denis Sh.; Terentyev, Anton O.; Shepelevich, Igor S.
Abstract : In contrast to the previous study, we report on no correlation between mean polarizability of fullerene derivatives and open-circuit voltages of organic solar cells based on them. Abstract : Though a linear correlation has been recently reported between mean polarizabilities of the fullerene derivatives and open-circuit voltages of organic solar cells based on them, we demonstrate that there is no general dependence between these two values and some related quantities (anisotropy of polarizability and LUMO levels).